Impact of lockdown in patients with congestive heart failure during the Covid-19 pandemic. (11th May 2021) - Chague, F; Boulin, M; Eicher, JC; Bichat, F; Saint-Jalmes, M; Cransac-Miet, A; Soudry, A; Danchin, N; Laurent, G; Cottin, Y; Zeller, M
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Dijon Football Côte d"Or OnBehalf: CLEO-CD Background: Congestive heart failure (CHF) can be destabilized by Covid-19 (C19) lockdown. Purpose: To evaluate the impact of lockdown in CHF patients. Methods: 150 out-patients from the HF Clinic of our hospital were invited to answer to a phone-call interview during the 7th week of first C19 lockdown . Results: From 124 questionnaires, more than 1/5 felt worse and almost 1/4 declared a psychologic distress. CHF medications were modified in 10%. Decrease in physical activity was observed in 2/5. Almost 1/2 declared increased screen time; smokers often increased consumption. Adherence to dietary counselling was reduced by 1/6, increase in weight and HF symptoms were common. Some patients benefitted from a teleconsultation. Conclusions: Our patients exhibited well-being impairment and unhealthy behaviours. Medication adherence was not diminished and the reduction in care access was counterbalanced by a switch toward telehealth.